Immunomodulatory Proteins in Tick Saliva From a Structural Perspective - Denisov, Stepan S.; Dijkgraaf, Ingrid (Frontiers in Cellular and Infection Microbiology, 2021)
To feed successfully, ticks must bypass or suppress the host’s defense mechanisms, particularly the immune system. To accomplish this, ticks secrete specialized immunomodulatory proteins into their saliva, just like many other blood-sucking parasites. However, the strategy of ticks is rather unique compared to their counterparts. Ticks’ tendency for gene duplication has led to a diverse arsenal of dozens of closely related proteins from several classes to modulate the immune system’s response. Among these are chemokine-binding proteins, complement pathways inhibitors, ion channels modulators, and numerous poorly characterized proteins whose functions are yet to be uncovered. Studying tick immunomodulatory proteins would not only help to elucidate tick-host relationships but would also provide a rich pool of potential candidates for the development of immunomodulatory intervention drugs and potentially new vaccines. In the present review, we will attempt to summarize novel findings on the salivary immunomodulatory proteins of ticks, focusing on biomolecular targets, structure-activity relationships, and the perspective of their development into therapeutics.